Input of organic matter in Brunei Bay, East Malaysia, as indicated by sedimentary steroids and multivariate statistics - Tay, Joo Hui; Pang, Swee Yun; Suhaimi, Suratman; Simoneit, B.R.T.; Norhayati, Mohd Tahir (Elsevier, 2020)
Brunei Bay is one of the most important marine environments of East Malaysia (South China Sea), covering many productive ecosystems with activities including fisheries, tourism, and main shipping lanes for petroleum transfers. Evaluation of the sources and distributions of steroids in the surface sedimentary organic matter was carried out by gas chromatography–mass spectrometry (GC–MS). The concentrations of the total identified sterols (TIS) ranged between 0.81 and 12.69 μg g−1 dry weight, and the total sterones were between 0.11 and 5.66 μg g−1 dry weight. The coprostanol level was comparatively low (<0.10 μg g−1), and the multi-biomarker proxies indicated that the region did not exhibit significant contamination from sewage effluents. Principal component analysis (PCA) revealed the coastal environment of the study area was dominated by allochthonous (mainly terrestrial) organic matter input.